Domination Number of Harary Graph - M Ulul Albab; Zainullah Zuhri (Universitas Islam Lamongan, 2023)
The domination number of graph Â is the smallest cardinality of the domination set of graph G. A subset of a vertex set S of G is called the domination set if every element of Â dominates every vertex of G, meaning that every vertex of G that is not an element of S is connected and one distance from S. The domination number has become interesting research studies on several graphs k -connected such as circulant graphs, grids, and wheels. This study aims to determine domination number of the other k-connected graph is Harary graph. The method used pattern detection and axiomatic deduction. The obtained results are new lemmas and theorems. The discussion obtained challenges new patterns of the smallest of domination number of Harary Graph, especially shape H_2,n, H_4,n, H_k,n and Â for every n vertices, k even integer, and k<n.